2005
DOI: 10.1136/bjo.2004.061275
|View full text |Cite
|
Sign up to set email alerts
|

Systolodiastolic variations of blood flow during central retinal vein occlusion: exploration by dynamic angiography

Abstract: Background/aim: In patients with acute central retinal vein occlusion (CRVO), dynamic angiography may reveal the presence of pulsatile flow (termed here pulsatile venular outflow, PVO) within first order veins (that is, the large veins). The main goal of this study was to investigate the mechanism underlying PVO. Methods: 10 patients with CRVO and PVO were included. Quantitative and qualitative analysis of venous flow on dynamic angiograms allowed the correlation, temporally, of second and first order vein flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…60,61 Interestingly, arteriovenous waveforms presented recently by Morgan et al 62 and measured in glaucomatous patients show a similar matching (data of Figure 3d after additional peak-to-peak normalization).…”
Section: Type 2: Matched Arteriovenous Waveforms (Subject S9)supporting
confidence: 53%
“…60,61 Interestingly, arteriovenous waveforms presented recently by Morgan et al 62 and measured in glaucomatous patients show a similar matching (data of Figure 3d after additional peak-to-peak normalization).…”
Section: Type 2: Matched Arteriovenous Waveforms (Subject S9)supporting
confidence: 53%
“…In future, however, new OCT modalities such as en face OCT angiography (OCT-A) may help to determine whether the middle retinal amplification of the ischaemic pathology is primarily a consequence of its exaggerated energy requirements or if it reflects preferential perfusion of the SCP (Tokayer et al, 2013). Of note, in eyes with CRVO, the superficial inner retina may be in receipt of additional oxygenation by convective (or "flow-assisted") diffusion related to the vigorous pulsation of the distended retinal vessels (Paques et al, 2005;Bertuglia et al, 2005). In this regard, the IPL may also have a role in restricting the movement of (oxygen-carrying) extracellular fluid into the middle retina (Antcliff et al, 2001), thus magnifying the differential susceptibility to hypoperfusion-induced damage.…”
Section: Grade 1 Hypoperfusion Maculopathymentioning
confidence: 98%
“…The serial organization of retinal layers provides a straightforward explanation for the localization of perivenular whitening in the DVP. [29][30][31] Indeed, there is angiographic evidence that the latter presentation is linked to panretinal hypoperfusion, 32 that is, severely impaired arterial inflow leading to a premature oxygen desaturation in precapillary arterioles. Our model suggested that perivenular whitening is initiated and/or more severe at the origin of draining venules (i.e., in the center of watersheds).…”
Section: Discussionmentioning
confidence: 99%